Recontextualizing Pesantren in International Scholarship: A Corpus-Based Semantic Profile Analysis - Ahmad Suhaili; Frans Sayogie; Muhammad Farkhan (Buletin Al-Turas, 2026)
Purpose Since the early 2000s, pesantren have been the most talked-about topic in international studies about Indonesian Islam. More and more Indonesian Islamic Higher Education Institutions are being published in academic journals around the world. This has made it easier for pesantren to be represented in Scopus-indexed journals, where these institutions are linked to a wide range of topics, from religious moderation to educational innovation. Since the term "pesantren" has gained significant traction in worldwide academia, it has been linked to a range of notions, from old Islamic boarding schools to contemporary higher education institutions. Method This study employs a specialized corpus of 6,774 peer-reviewed articles from Scopus-indexed journals of Indonesian Islamic Higher Education Institutions (2015-2025) to examine the representation of pesantren in international scholarship through semantic prosody and semantic preference analysis within the Corpus-Assisted Discourse Studies (CADS) framework. Semantic preference identifies the semantic sets associated with the node word 'pesantren' throughout two temporal periods, while semantic prosody analyzes the evaluative context in which the node word appears. An artificial semantic tagger called the UCREL Semantic Analysis System (USAS) is used to find the semantic preference by giving the collocations semantic labels. Result The semantic prosody is then found by looking at the concordance lines. The study finds that the word "pesantren" in Period I (2015–2020) is more likely to be linked to traditional Islamic education, institutional identity, and charismatic leadership. In Period II (2021–2025), it is more likely to be linked to organizational management, higher education, and religious moderation discourse. It also shows that the node word has mostly good prosody in both periods, but that the quality changes from cultural preservation to institutional transformation. Conclusion International scholars are increasingly seeing pesantren in a positive light, not just as conventional schools but also as flexible, adaptable organizations that deal with modern problems like modernization, digitalization, and social growth.